2014
DOI: 10.1097/mop.0000000000000087
|View full text |Cite
|
Sign up to set email alerts
|

Maternal–fetal cellular trafficking

Abstract: Purpose of review Maternal-fetal cellular trafficking (MFCT) is the bidirectional passage of cells between mother and fetus during pregnancy. This results in the presence of fetal cells in the maternal circulation, known as fetal microchimerism, and maternal cells in the fetal circulation, known as maternal microchimerism. The biologic role of this bidirectional passage of cells during pregnancy is not known, although it has been implicated in development of the fetal immune system, tolerance mechanisms during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(27 citation statements)
references
References 82 publications
1
23
0
2
Order By: Relevance
“…A notable finding of this paper is that maternal micro-chimerism was more profound in these preterm babies, thus providing additional evidence of inflammation-driven increase in maternal micro-chimerism. The same authors reported earlier that fetuses with severe congenital diaphragmatic hernia, who exhibit high inflammatory cytokines in cord blood, also have increased maternal micro-chimerism (7); a similar increase was also described in babies exposed to placental malaria (8). Interestingly, the latter study showed that both malaria infection and inflammation contributed to this enhanced transfer of maternal cells.…”
supporting
confidence: 65%
“…A notable finding of this paper is that maternal micro-chimerism was more profound in these preterm babies, thus providing additional evidence of inflammation-driven increase in maternal micro-chimerism. The same authors reported earlier that fetuses with severe congenital diaphragmatic hernia, who exhibit high inflammatory cytokines in cord blood, also have increased maternal micro-chimerism (7); a similar increase was also described in babies exposed to placental malaria (8). Interestingly, the latter study showed that both malaria infection and inflammation contributed to this enhanced transfer of maternal cells.…”
supporting
confidence: 65%
“…It has been shown that maternal alloantigens cross the placenta [65] and potently induce foetal T regulatory cells [66]. Whether this transfer occurs through intact maternal cells or through EVs remains to be shown, but the latter seems to be a reasonable assumption as intact cells might be more susceptible to mechanical and immunological foetal barriers [67]. In this context, it is also of interest to determine whether EVs derived from the maternal microbiome can cross the placenta and exhibit immune modulating properties.…”
Section: Evs In Homeostasismentioning
confidence: 99%
“…Moreover, VUE is histologic evidence of maternal cell trafficking into the fetus, which could lead to the development and establishment of fetal-maternal microchimerism 79 . It remains to be established if maternal T cells are grafted into the visceral organs of the fetus.…”
Section: Chronic Nonspecific Villitis (Villitis Of Unknown Etiologymentioning
confidence: 99%